Communication Strategy Based on Interactive Games in Climate Change Education by Predikt Tangguh Indonesia - Annisaa Larasati Oetomo; Wahyu Budi Priatna (Indonesian Scientific Publication, 2026)
This study analyzes PT Predikt Tangguh Indonesia’s communication strategy for climate change education, focusing on the innovative integration of the GenerAksi board game and Instagram-based edutainment media. By employing interactive and participatory two-way communication, these approaches enhance audiences’ understanding, engagement, and motivation toward climate action. GenerAksi promotes collaborative experiential learning, enabling participants to explore climate risks and solutions in relatable real-life scenarios. Meanwhile, Instagram expands outreach and stimulates continuous involvement in climate discussions. Unlike dominant climate education approaches that remain one-way and school-centered, this study highlights the novelty of combining offline and digital interactive platforms as a unified community-oriented communication method. The findings provide insight into how innovative communication strategies can strengthen public awareness and meaningful participation in climate change education in Indonesia.